INTEGRASI VSM DAN VALSAT DI LEAN MANUFACTURING UNTUK KURANGI WASTE DI PT. SPLN - Kurniawan, Moh. Arif; Apriliana Sari Wulandari, Indah (Universitas Muhammadiyah Sorong, 2024)
Maximizing productivity and quality of products produced by a company is very necessary, an approach that can optimize the use of human resources and production equipment. An approach that has proven to be very good at reducing waste is Lean Manufacturing. In this research, the method used to minimize waste at PT. SPLN is Value Stream Mapping (VSM) and Value Stream Analysis Tools (VALSAT). VSM is used to view the condition map of each workstation in the company. Waste reduction is carried out using one of the tools from VALSAT, namely process activity mapping (PAM). After the improvements were made, there was a significant change in the number of cable trays produced, increasing from 138 units to 172 units. Number of Necessary but Not Value Added (NNVA) found in PT's production process. SPLN is 70.54% followed by Non Value Added (NVA) with a total of 29.04% and value added (VA) of 0.03%. The proposed improvement is to reduce the amount of time for NNVA and NVA activities or eliminate them.